The medieval world. - Armstrong, Dorsey, 1970-; Teaching Company (Chantilly, Va. : Teaching Co., 2009)
"Between the fall of the Roman Empire and the brief, brilliant cultural phenomenon we call the Renaissance lay the Middle Ages - fully 1,000 years of artistic, philosophical, political, and religious turmoil and treasures. This course offers an interdisciplinary look at medieval society and culture, with an emphasis on literature, the arts, and the tumultuous historical forces at work from A.D. 500 through A.D. 1500. Medieval Europe was the world of cathedrals and universities; pilgrimages and saints; the Black Death; The Vikings; the spread of Islam; the Crusades; and the forging of the Greek, Latin, Old Norse, and ancient Germanic and Celtic tongues into the languages we speak today"--Publisher provided.
Part 1: Lecture 1: The Medieval world -- Lecture 2: The legacy of the Roman world -- Lecture 3: The Christianization of Europe -- Lecture 4: After the Roman Empire: hybrid cultures -- Lecture 5: Early monasticism -- Lecture 6: From Merovingian Gaul to Carolingian France -- Lecture 7: Charlemagne and the Carolingian Renaissance -- Lecture 8: Byzantium, Islam, and the West -- Lecture 9: The Viking invasions -- Lecture 10: Alfred the Great -- Lecture 11: The rearrangement of the medieval world -- Lecture 12: The Norman conquest and the Bayeux tapestry -- Part 2: Lecture 13: King Arthur: the power of the legend -- Lecture 14: The three orders of medieval society -- Lecture 15: Pilgrimage and sainthood -- Lecture 16: Knighthood and heraldry -- Lecture 17: The Gothic cathedral -- Lecture 18: Piety, politics, and persecution -- Lecture 19: The persistence of an ideal -- Lecture 20: Late medieval religious institutions -- Lecture 21: The Magna Carta -- Lecture 22: Daily life in a noble household -- Lecture 23: Daily life in a medieval village -- Lecture 24: Medieval city life -- Part 3: Lecture 25: Food and drink -- Lecture 26: Music and entertainment -- Lecture 27: Dress and fashion -- Lecture 28: Medieval medicine -- Lecture 29: The Black Death and its effects -- Lecture 30: Childhood in the Middle Ages -- Lecture 31: Marriage and the family -- Lecture 32: Art and artisans -- Lecture 33: Science an technology -- Lecture 34: Weapons and warfare -- Lecture 35: Revolts, uprisings, and wars -- Lecture 36: Toward the early modern period.
Taught by professor Dorsey Armstrong of Purdue University.
"Ancient & medieval history"--Container.
Course No. 8280.
36 half-hour lectures with lecture transcripts in one guidebook.
DVD.
Keywords: Civilization, Western -- History; Civilization, Medieval; Middle Ages; Speeches, addresses, etc; Instructional films; Educational films